Constructing the Quality Measurement Model of Street Space and Its Application in the Old Town in Wuhan - Wan, Tianyue; Lu, Wei; Sun, Peijin (Frontiers in Public Health, 2022)
The quality of street space is the comprehensive suitability evaluation from objective physical environments and subjective pedestrian perception. Since existing quality measurement models of street space do not consider both subjective and objective aspects, it is difficult for planners to accurately locate low-quality streets that need to be regenerated. To solve this problem, this study proposes a new 5D+3S measurement model for street space quality evaluation. This model incorporates the widely acknowledged 5D dimensions of the physical environments (Design, Destination accessibility, Distance to transit, Density, and Diversity), and the 3S dimensions (Sociality, Safety, and Status) of walking perception derived from keywords clustering on relevant literature. To test the validity of the proposed model, this study makes a comparative analysis on the results of the public assessment, expert scoring, and model measurement to verify whether the measurement results are objective and convincing. The results show that the quality grade obtained by the proposed measurement model is highly consistent with the subjective evaluation outcomes of the public and experts. Thus, the proposed measurement model is effective in quality measurement of street space, which provides a new idea for future large-scale diagnosis of city public space quality.